2012
DOI: 10.5796/electrochemistry.80.974
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of Carbon Tetrachloride and Mono-Chlorobenzen by Using Basic Molten Salts

Abstract: The decomposition of simple organic chlorides (carbon tetrachloride, CCl 4 and mono-chlorobenzen, C 6 H 5 Cl) as the imitation substances of polychlorobiphenyls (PCBs) were investigated by using basic molten salts with a low melting point and oxidizing ability in order to establish a safe, simple and highly efficient decomposition process. CCl 4 or C 6 H 5 Cl was injected together with an inert carrier gas (Ar) into basic molten salts (KOH-K 2 CO 3 ) at 673-983 K, and the residual concentration in the exhaust … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…It is also possible that the oxide ion reacts with the small molecules generated from the thermal degradation of PTFE to promote the formation of F − and CO 2 . It has also been found that molten MOH is a particularly effective agent for the decomposition of small organic compounds containing halogen or sulfur, such as CCl 4 , 27 chlorobenzene, 28 coal, 29 and even hazardous mixed organic waste. 30 Thus, as shown in eqn (6), if our system progresses ideally, PTFE can be processed without the generation of exhaust gases and can be efficiently mineralized.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also possible that the oxide ion reacts with the small molecules generated from the thermal degradation of PTFE to promote the formation of F − and CO 2 . It has also been found that molten MOH is a particularly effective agent for the decomposition of small organic compounds containing halogen or sulfur, such as CCl 4 , 27 chlorobenzene, 28 coal, 29 and even hazardous mixed organic waste. 30 Thus, as shown in eqn (6), if our system progresses ideally, PTFE can be processed without the generation of exhaust gases and can be efficiently mineralized.…”
Section: Resultsmentioning
confidence: 99%
“…For example, while hydroxide melts are believed to be fully dissociated, the formation of a "quasi-crystalline state" has also been described, in which a degree of order exists within the melt and dissociation is not complete. 27 Thus, at present, we do not have sufficient experimental evidence to understand the difference between the reactivities of molten NaOH and molten KOH toward PTFE. We recognize that this is an important subject to be addressed in the near future.…”
Section: ð4þmentioning
confidence: 94%
See 1 more Smart Citation
“…Acidic gases such as HX and SO 2 are absorbed and neutralized by the molten salt, reducing the need for off-gas desulphurization and deacidification equipment [27]. The absence of chlorine in the exhaust gas inhibits the synthesis reaction of PCDD/F, leading to the decomposition and destruction of dioxin precursors in the molten salt, thereby eliminating the precursor synthesis pathway of PCDD/F [28,29]. Last but not least, molten salt has a high heat capacity, which helps to minimize the impact of temperature and feed fluctuations on the reaction process due to the thermally stable environment provided by the salt bath [30].…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14] The advantages of utilization of molten salts are summarized as follows: (1) no dioxins are formed due to gas/liquid separation, and only simple harmless products (CO 2 and H 2 O) are emitted; (2) operation temperature is considerably lower than that in the conventional incineration, and the temperature control is easy because of the reaction in condensed phase; (3) decomposition treatment is carried out under atmospheric pressure; (4) handling of chlorine absorber (molten salts) is easy. The authors have studied the decomposition of carbontet-© 2012 ISIJ rachloride (CCl4) 3) and mono-, di-and tri-chlorobenzens 4) as a simple chlorinated organic compound prior to the decomposition of PCBs. As the results, CCl4 was destructed at high decomposition efficiency over 99.9% at relatively low temperature (673-973 K) without oxygen.…”
Section: Introductionmentioning
confidence: 99%